A concretização do direito fundamental ao meio ambiente ecologicamente equilibrado: um exame a partir de ações estatais - Diógenes, José Lenho Silva (2011)
The environmental protection has won seat in Article 225 of the Constitution of the Federative Republic of Brazil of 1988. Nowadays, there is a doctrinal and jurisprudential consensus that, despite this constitutional provision not to have had forecast in the chapter on rights and individual and collective duties, it's about a typical fundamental right. In this sense, his legal approach calls for the adoption of a theory compatible with the complex structure of fundamental rights. Thus, this dissertation is concerned with examining the process of realizing the fundamental right to an ecologically balanced environment from the theory of fundamental rights. To this end, some considerations are made about this theory. From there, we try to understand the structure and content of the clause of Article 225 of the Constitution of 1988; the factual support; the ambit of protection and the possibility of restrictions on the fundamental right enshrined by this rule, as well as the functions of even in the Brazilian legal system. In particular, we analyze the functions that describe it as a right to state benefits in a broad sense and as a right of defense. Finally, we seek to understand how that process of realizing has been occurred, with reference to positive state action to preserve the environment and the restrictions to the same arising from Brazilian energy use. The methodology used is bibliographic, descriptive, exploratory and case law.